Angioedema without urticaria: novel findings which must be measured in clinical setting. Issue 3 (June 2020) - Veronez, Camila Lopes; Grumach, Anete Sevciovic
Abstract : Purpose of review: Angioedema without urticaria is composed of an increasing subtype's variety and presents a challenging diagnosis. This review summarizes the subtypes recently described and subsequent new findings helpful within their classification. Recent findings: New methods to measure cleaved high molecular weight kininogen and activated plasma kallikrein have emerged as potential biochemical tests to identify bradykinin-mediated angioedema. Three new subtypes of hereditary angioedema (HAE) with normal C1 inhibitor were described in the past two years: HAE due to mutation in plasminogen gene, in kininogen gene, and in angiopoietin-1 gene; implicating the fibrinolytic and contact systems, and the regulation of vasculature, respectively. The understanding of some mechanisms in angioedema has been improved, compatible to the dominant-negative for some C1 inhibitor variants; furthermore, the increased activation of truncated F12 mutants by plasma kallikrein; and the diminished binding of angiopoietin-1 to its receptor. Summary: The validation of biomarkers for the contact system activation could be beneficial in differentiating bradykinin – from histaminergic-mediated angioedema. Currently, the available laboratorial tests are still somewhat restricted to the evaluation of the complement activation and the mediators of nonhistaminergic and nonbradykinin-mediated angioedema remain to be identified.